2006
DOI: 10.1038/oby.2006.193
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Fatness Patterns in Prader‐Willi Syndrome: Comparison with Simple Obesity

Abstract: Research Methods and Procedures: Seventy-two individuals (27 PWS deletion, 21 PWS uniparental disomy, and 24 obese controls) 10 to 49 years old were studied with the use of DXA. Body composition measures were obtained, and regional fat and lean mass patterns were characterized. Significant differences were assessed with Student's t test and ANOVA adjusting for age, gender, and BMI. Results: Significant differences between the PWS and obese groups were found for lean measures of the arms, legs, and trunk. Total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
6
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 19 publications
3
73
6
1
Order By: Relevance
“…Interestingly, the two groups were also matched for central adiposity and insulin resistance without specific selection of control subjects. Although our PWS cohort might seem unusual, as a lower visceral fat mass and preserved insulin sensitivity has been reported previously (Brambilla et al, 1997, Goldstone et al, 2001, Goldstone et al, 2004, Goldstone et al, 2005, Talebizadeh and Butler, 2005, Kennedy et al, 2006, Theodoro et al, 2006, Haqq et al, 2010and Sode-Carlsen et al, 2010, other investigators recently reported similar observations to ours, i.e. obese children and adults with PWS having the same amount of visceral fat mass, the same degree of insulin resistance and a similar prevalence of metabolic syndrome compared to carefully weight-matched obese subjects Butler, 2005 andBrambilla et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, the two groups were also matched for central adiposity and insulin resistance without specific selection of control subjects. Although our PWS cohort might seem unusual, as a lower visceral fat mass and preserved insulin sensitivity has been reported previously (Brambilla et al, 1997, Goldstone et al, 2001, Goldstone et al, 2004, Goldstone et al, 2005, Talebizadeh and Butler, 2005, Kennedy et al, 2006, Theodoro et al, 2006, Haqq et al, 2010and Sode-Carlsen et al, 2010, other investigators recently reported similar observations to ours, i.e. obese children and adults with PWS having the same amount of visceral fat mass, the same degree of insulin resistance and a similar prevalence of metabolic syndrome compared to carefully weight-matched obese subjects Butler, 2005 andBrambilla et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…7 Nearly 1 of every 3 individuals with PWS are more than 200% of their ideal body weight, and some have even experienced stomach ruptures from overconsumption. 76 The metabolic physiology of PWS differs from obesity in normal individuals, such as increased ratio of adiposity to lean mass, 81 decreased total and resting energy expenditure, 8 and 4 times greater fasting ghrelin levels. 33 PWS is a difficult to treat syndrome that has not benefited from the most radical medical and surgical interventions.…”
Section: Prader-willi Syndromementioning
confidence: 99%
“…Theodoro et al (2006) looked at studies comparing individuals with PWS and obese subjects, and reported differences in the lean mass of trunk and limbs; people with PWS demonstrated an unusual body composition and unusual fatness patterns.…”
Section: Hyperphagiamentioning
confidence: 99%